Essentials of terrorism: concepts and controversies - Martin, Gus (SAGE, 2017)
About the author -- Preface -- Acknowledgments -- Understanding terrorism: a conceptual review -- Defining terrorism -- Historical perspectives and ideological origins -- Causes of terrorist violence -- Terrorist violence and the role of the media -- Terrorist environments -- Terrorism by the state -- Terrorism by dissidents -- Religious terrorism -- International terrorism -- Domestic terrorism in the united states -- The terrorist battleground -- Counterterrorism and the war on terrorism -- Homeland security -- Future trends and projections -- Appendix a: map references -- Appendices -- Photo credits -- Glossary -- Notes -- Index